Public Private Partnership Dalam Implementasi Program Corporate Social Responsibility (Studi Pembentukan Kelembagaan Komunitas Menuju Kemandirian) - Riyandi Firdaus, Muhammad; Noor , Muhammad; Suparti, Heni (stiatabalong.ac.id, 2025)
The presence of PT. Adaro Indonesia, a private sector entity operating in the coal mining sector in Tabalong Regency, has an impact on the environment as a whole, including the community. The company's activities have thus encouraged the emergence of the concept of social responsibility to empower the community in Harus Village. The lack of proper policy synchronization between the government and businesses, coupled with low company commitment and limited community communication and participation, often hinders the effectiveness of CSR program implementation. Therefore, establishing sound cooperation and partnership models is crucial. This study employs a qualitative approach with a case study method. The research was conducted in Harus Village, Tabalong Regency, South Kalimantan Province, which is a beneficiary of PT. Adaro Indonesia's CSR program. The findings indicate that the public-private partnership in the CSR program is functioning well. This is evidenced by the accountability, transparency, and sustainability built upon the commitment, cooperation, and synergy of various stakeholders in implementing the CSR program, resulting in a sustainable impact for the community. This research recommends that increased involvement of the private sector in institutional and community development can reduce the dominance of government roles, thereby ensuring that policy processes through CSR programs originate from public participation (top-down policy).